2020
DOI: 10.1007/s10126-020-09978-z
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Genetic Engineering of a Unicellular Green Alga Haematococcus pluvialis with Expression of an Antimicrobial Peptide

Abstract: The purpose of this study was to express an antimicrobial peptide in the chloroplast to further develop the plastid engineering of H. pluvialis. Homologous targeting of the 16S-trnI/trnA-23S region and four endogenous regulatory elements, including the psbA promoter, rbcL promoter, rbcL terminator, and psbA terminator in H. pluvialis, were performed to construct a chloroplast transformation vector for H. pluvialis. The expression of codon-optimized antimicrobial peptide piscidin-4 gene (ant1) and selection mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…It is generally accepted that a lack of homology in the flanking sequences may result in lower recombination rates [ 27 ]. In this study, 16S rDNA/ trnA -23S was selected as the homologous insertion site, which is widely used for gene insertion in chloroplast transformation, such as in Haematococcus pluvialis [ 28 ], Tisochrysis lutea [ 29 ], Platymonas Subcordiformis [ 30 ], Momordica charantia L [ 31 ]. Some studies have shown that trnI / trnA is an effective gene insertion locus in the chloroplast genome [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that a lack of homology in the flanking sequences may result in lower recombination rates [ 27 ]. In this study, 16S rDNA/ trnA -23S was selected as the homologous insertion site, which is widely used for gene insertion in chloroplast transformation, such as in Haematococcus pluvialis [ 28 ], Tisochrysis lutea [ 29 ], Platymonas Subcordiformis [ 30 ], Momordica charantia L [ 31 ]. Some studies have shown that trnI / trnA is an effective gene insertion locus in the chloroplast genome [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microalgae represent an important biotechnology resource for the production of recombinant proteins for pharmacological applications. Successful results were reported by the genetic manipulation of microalgae for the production of antigens for vaccines, antibodies, immunotoxins, hormones, and antimicrobial agents [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Strategies and techniques have been developed for the exploitation of microalgae as expression systems for a number of advanced genetic toolkits [ 62 , 63 , 64 , 65 ].…”
Section: Microalgae Engineering For the Production Of Pharmacological Proteinsmentioning
confidence: 99%
“…An interesting example of antimicrobial peptide against both fish and human pathogens is piscidin-4. This was recently produced in H. pluvialis by biolistic manipulation of chloroplast of this microalga [ 81 ].…”
Section: Microalgae Engineering For the Production Of Pharmacological Proteinsmentioning
confidence: 99%
“…Transformation of S. obliquus via A. tumefasciens is feasible (Suttangkakul et al, 2019 ). Both nuclear and chloroplastic transformations have been described for H. pluvialis (Yuan et al, 2019 ; Wang et al, 2020 ; Cui et al, 2021 ). Finally, Charophyta are Green Algae close to Embryophyta, propagating by haploid asexual division; sexual reproduction is known.…”
Section: Challenges In Microalgae Domesticationmentioning
confidence: 99%